![image](https://tex.z-dn.net/?f=%20%28%5Cfrac%7B3%7D%7B4%7D%20%20%2B%20%20%5Cfrac%7B1%7D%7B2%7D%20%20%2B%20%20%5Cfrac%7B5%7D%7B12%7D%29%20%20%5Ctimes%2012%20%3D%20%20%5Cfrac%7B%283%20%5Ctimes%203%20%2B%20%201%5Ctimes%206%20%2B%205%29%20%5Ctimes%2012%7D%7B12%7D%20%20%20%3D%209%20%2B%206%20%2B%205%20%3D%2020%20%20%20%5C%5C%20%5C%5C%2024%20%5Ctimes%20%28%20%5Cfrac%7B1%7D%7B2%7D%20%20%2B%20%20%5Cfrac%7B3%7D%7B8%7D%20%20%2B%20%20%5Cfrac%7B5%7D%7B6%7D%20%29%20%3D%20%20%5Cfrac%7B24%20%5Ctimes%20%2812%20%2B%203%20%5Ctimes%203%20%2B%205%20%5Ctimes%204%29%7D%7B24%20%7D%20%20%3D%2012%20%2B%209%20%2B%2020%20%3D%2041%20%5C%5C%20%5C%5C%20%20%3C%2Fp%3E%3Cp%3E4%20%5Ctimes%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%2B%204%20%5Ctimes%20%20%5Cfrac%7B2%7D%7B5%7D%20%20%2B%204%20%5Ctimes%20%20%5Cfrac%7B2%7D%7B15%7D%20%20%3D%204%20%5Ctimes%20%28%20%5Cfrac%7B1%7D%7B3%7D%20%20%2B%20%20%5Cfrac%7B2%7D%7B5%7D%20%20%20%2B%20%20%5Cfrac%7B2%7D%7B15%7D%20%29%20%3D%204%20%5Ctimes%20%20%5Cfrac%7B5%20%2B%202%20%5Ctimes%203%20%2B%202%7D%7B15%7D%20%20%3D%204%20%5Ctimes%20%20%5Cfrac%7B5%20%2B%206%20%2B%202%7D%7B15%7D%20%20%3D%20%20%5Cfrac%7B4%20%5Ctimes%2013%7D%7B15%7D%20%20%5Cfrac%7B52%7D%7B15%7D%20%20%3D%203%20%5Cfrac%7B7%7D%7B15%7D%20%20%20%5C%5C%20%5C%5C%20%3C%2Fp%3E%3Cp%3E7%20%5Ctimes%20%20%5Cfrac%7B2%7D%7B3%7D%20%20%2B%207%20%5Ctimes%20%20%5Cfrac%7B1%7D%7B2%7D%20%20%2B%207%20%5Ctimes%20%20%5Cfrac%7B5%7D%7B6%7D%20%20%3D%207%20%5Ctimes%20%28%20%5Cfrac%7B2%7D%7B3%7D%20%20%2B%20%20%5Cfrac%7B1%7D%7B2%7D%20%20%2B%20%20%5Cfrac%7B5%7D%7B6%7D%29%20%20%3D%207%20%5Ctimes%20%20%5Cfrac%7B2%20%5Ctimes%202%20%2B%203%20%2B%205%7D%7B6%7D%20%20%3D%207%20%5Ctimes%20%20%5Cfrac%7B12%7D%7B6%7D%20%20%3D%207%20%5Ctimes%202%20%3D%2014)
4 \times \frac{1}{3} + 4 \times \frac{2}{5} + 4 \times \frac{2}{15} = 4 \times ( \frac{1}{3} + \frac{2}{5} + \frac{2}{15} ) = 4 \times \frac{5 + 2 \times 3 + 2}{15} = 4 \times \frac{5 + 6 + 2}{15} = \frac{4 \times 13}{15} \frac{52}{15} = 3 \frac{7}{15} \\ \\
7 \times \frac{2}{3} + 7 \times \frac{1}{2} + 7 \times \frac{5}{6} = 7 \times ( \frac{2}{3} + \frac{1}{2} + \frac{5}{6}) = 7 \times \frac{2 \times 2 + 3 + 5}{6} = 7 \times \frac{12}{6} = 7 \times 2 = 14" alt=" (\frac{3}{4} + \frac{1}{2} + \frac{5}{12}) \times 12 = \frac{(3 \times 3 + 1\times 6 + 5) \times 12}{12} = 9 + 6 + 5 = 20 \\ \\ 24 \times ( \frac{1}{2} + \frac{3}{8} + \frac{5}{6} ) = \frac{24 \times (12 + 3 \times 3 + 5 \times 4)}{24 } = 12 + 9 + 20 = 41 \\ \\
4 \times \frac{1}{3} + 4 \times \frac{2}{5} + 4 \times \frac{2}{15} = 4 \times ( \frac{1}{3} + \frac{2}{5} + \frac{2}{15} ) = 4 \times \frac{5 + 2 \times 3 + 2}{15} = 4 \times \frac{5 + 6 + 2}{15} = \frac{4 \times 13}{15} \frac{52}{15} = 3 \frac{7}{15} \\ \\
7 \times \frac{2}{3} + 7 \times \frac{1}{2} + 7 \times \frac{5}{6} = 7 \times ( \frac{2}{3} + \frac{1}{2} + \frac{5}{6}) = 7 \times \frac{2 \times 2 + 3 + 5}{6} = 7 \times \frac{12}{6} = 7 \times 2 = 14" align="absmiddle" class="latex-formula">